Where science and ethics meet : dilemmas at the frontiers of medicine and biology - Willmott, Chris; Macip, Salvador (Praeger, an imprint of ABC-CLIO, LLC, 2016)
"Recent biomedical discoveries promise considerable improvement in the quality of human life, but they also hold the potential to permanently alter society. Are the anticipated benefits worth the price we would have to pay for them? In Where Science and Ethics Meet: Dilemmas at the Frontiers of Medicine and Biology, a biochemist and a biomedical researcher who are highly experienced in explaining ethics for lay audiences present the most innovative advances in biomedicine and enable readers to develop their own opinions about the ethical and social consequences these technologies will bring. Each controversial topic in modern medicine and ethics is introduced through a hypothetical case study that highlights thorny ethical issues before explaining the key aspects of the science and technology involved and addressing the associated ethical considerations in detail."--Publisher's description